TEORI, KONSEP DAN RUANG LINGKUP PEDIDIKAN ISLAM KONTEMPORER - Sukari; Nur Aziz; Mudzakir Chabib (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
Contemporary Islamic education faces various challenges due to the rapid development of science, technology, and social change. This condition requires the formulation of theories, concepts, and the scope of Islamic education that are adaptive while remaining grounded in Islamic values. This article aims to examine the theories, concepts, and scope of contemporary Islamic education as a foundation for developing Islamic education that is relevant to the demands of the times. This study employs a library research method with a descriptive-analytical approach to literature related to contemporary Islamic education. The findings indicate that contemporary Islamic education is based on the integration of revelation and reason, emphasizes a balance between spiritual, intellectual, and social aspects, and encompasses a scope that includes educational objectives, curriculum, learning methods, educators, learners, and educational environments. This study is expected to contribute theoretically to the development of Islamic education studies and to serve as a reference for Islamic education practitioners in addressing the dynamics of modernity.